The development of digital educational materials on tribology and their application in the formation of the professional competence of future physics teachers - Nurizinova, Мakpal; Skakov, Мazhyn; Çoruh, Ali; Ramankulov, Sherzod; Nurizinov, Marat (International Journal of Innovative Research and Scientific Studies, 2024)
Tribology, as a science that studies friction in mechanisms and their wear, occupies an important place in the combination of education, science and industry. Therefore, the training of future physics teachers in the field of tribology is one of the urgent issues. The purpose of this study is to increase the effectiveness of teaching in the field of tribology and to evaluate the effectiveness of digital education in forming the professional competencies of students in this field. This research also used the methods of modeling in a digital environment, software and constructive design along with the methods of theoretical analysis. In addition, a pedagogical experiment was conducted in which 86 students participated. The learning outcomes were assessed using questionnaires. As a result of the research, an elective course “Physical Foundations of Tribology” was developed and digital resources for the discipline are included in the educational program. The results showed that the students in these programs have a high level of professional creativity and a positive attitude towards creative educational activities. They are also sufficiently prepared to use digital learning materials for this course (M = 3.89). The educational and methodological test showed how well e-learning resources have been developed to help students master the discipline of tribology at a professional level. This is evidenced by the fact that about 75% of students demonstrated a high level of professional knowledge and abilities. The results of the study are recommended to be used at all stages of training future teachers.